The Routledge handbook of Shakespeare and animals - Raber, Karen, 1961-; Dugan, Holly, 1975- (Routledge literature handbooks., 2021)
Shakespeare's plays have a long and varied performance history. The relevance of his plays in literary studies cannot be understated, but only recently have scholars been looking into the presence and significance of animals within the canon. Readers willquickly find--without having to do extensive research--that the plays are teeming with animals! In this Handbook, Karen Raber and Holly Dugan delve deep into Shakespeare's World to illuminate and understand the use of animals in his span of work. This volume supplies a valuable resource, offering a broad and thorough grounding in the many ways animal references and the appearance of actual animals in the plays can be interpreted. It provides a thorough overview; demonstrates rigorous, original research; and charts new frontiers in the field through a broad variety of contributions from an international group of well-known and respected scholars.